التبني في الإسلام - Nurbaiti bt Miskan; نور بيتي بنت ميسكان (Kolej Universiti Islam Malaysia, 2022)
This research deals with child adoption in the Islamic perspective. It discussed about various problems namely " nasab " or the status of parenthood, inheritance of properties and their responsibilities towards the adoptive parents . As stated in the Al-Quran and As-Sunnah among their responsibilities are to take care and repay their adoptive parents good deeds. In return, their adoptive parents should provide the adoptive child with education and to treat the child fairly since the child is gift from Allah. The researchers also discuses about the limitation in the aspect of " aurah " between the child and the adoptive parents with that of own child according to the Syariah Law regarding parenthood of adoptive child is fair and just.